Peripheral soft tissue Ewings sarcoma: a rare case report (Ibrahim Medical College Journal, 2014)
A 22 years male patient presented with gradual left forearm swelling for 6 months. X ray forearm revealed large soft tissue swelling with tiny calcification and mild scalloping at inner aspect of ulna and ultrasonogram (USG) revealed soft tissue mass having calcification and necrotic areas within and spectral Doppler showed arterial type of blood flow with no augmentation. Later computerized tomography (CT) scan showed soft tissue mass with necrotic area and calcification with no bony involvement. Magnetic resonance imaging (MRI) with contrast revealed a large heterogeneously enhancing lobulated mixed intensity lesion in antero-medial compartment of the left forearm involving flexor group of muscles causing displacement of fat plane. MRI and subsequent histopathology of the lesion revealed it as a rare soft tissue Ewings sarcoma / primitive neuroectodermal tumor (PNET) in extremity. DOI: http://dx.doi.org/10.3329/imcj.v7i2.20113 Ibrahim Med. Coll. J. 2013; 7(2): 43-46